The Importance of Guidance and Counseling in Elementary Schools for Student Development - Syeha Bagja Ubaydillah; Didit Ruhdianto; Neng Huriah Latipah; Nurfitriani (Aslim: Journal of Education and Islamic Studies, 2025)
The aim of this research is to understand the significance of guidance and counseling services at the elementary school level on student development. This type of research is qualitative using interview instruments. The subjects of this research were four elementary school class teachers. The research results show that: (1) It is very important and necessary to implement counseling guidance services in elementary schools which are run directly by guidance and counseling teachers. The aim is to help students complete their developmental tasks, overcome problems or obstacles they face, so that they can develop as individuals complete with their needs, actualize themselves, develop talents and interests, and express all their potential. (2) Even though class teachers have a dual role as guidance and counseling teachers, they must continue to improve their knowledge and skills in assisting and understanding the needs and characteristics of students in their classes. (3) There are still many challenges faced in elementary schools, therefore, cooperation between class teachers, guidance and counseling teachers and parents is very necessary to accompany and guide students in completing their developmental tasks well.